2011
DOI: 10.1002/ccd.22933
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration coronary thrombectomy for acute myocardial infarction increases myocardial salvage

Abstract: Aspiration thrombectomy improves myocardial salvage in high risk STEMI patients with angiographic evidence of thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 33 publications
1
31
1
1
Order By: Relevance
“…208 Also, no reduction of microvascular obstruction and infarct size was found with MRI. [209][210][211] Hyperoxemia, 212,213 aspiration or mechanical thrombectomy, [214][215][216][217][218][219][220][221] and intra-aortic balloon counterpulsation 222 did not reduce infarct size or improve coronary blood flow. More recently, also the cardioprotection by cyclosporine A which had been shown in a small-scale proof-of-concept trial 223 was not confirmed in another smaller study with prethrombolytic cyclosporine A 224 and, importantly, not in 2 larger-scale phase III trials, Does Cyclosporine Improve Clinical Outcome in ST Elevation Myocardial Infarction Patients (CIRCUS) and CyclosporinE A in Reperfused Myocardial Infarct (CYCLE).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…208 Also, no reduction of microvascular obstruction and infarct size was found with MRI. [209][210][211] Hyperoxemia, 212,213 aspiration or mechanical thrombectomy, [214][215][216][217][218][219][220][221] and intra-aortic balloon counterpulsation 222 did not reduce infarct size or improve coronary blood flow. More recently, also the cardioprotection by cyclosporine A which had been shown in a small-scale proof-of-concept trial 223 was not confirmed in another smaller study with prethrombolytic cyclosporine A 224 and, importantly, not in 2 larger-scale phase III trials, Does Cyclosporine Improve Clinical Outcome in ST Elevation Myocardial Infarction Patients (CIRCUS) and CyclosporinE A in Reperfused Myocardial Infarct (CYCLE).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…4,5,[12][13][14][15][26][27][28][29][30][31][32][33][34][35][36][37] The weighted mean follow-up duration was 3.7±2.7 months. Three trials reported outcomes at both 1 and 12 months.…”
Section: Included Studiesmentioning
confidence: 99%
“…4 The remaining 4 studies did not specifically define MACE. 5,[28][29][30] All the studies that reported complete ST-segment resolution used the cutoff ≥70%, 4,[12][13][14]26,[28][29][30][31][34][35][36][37] except for 1 study that used ≥50%. 32 Seven studies defined successful reperfusion as TIMI blush grade of 3, 13,14,26,29,32,34,35 whereas 5 studies used TIMI blush grade of ≥2.…”
Section: Included Studiesmentioning
confidence: 99%
“…Ciszewski et al 48 also reported encouraging results with aspiration thrombectomy. A total of 137 patients with first STEMI were randomized to either aspiration thrombectomy followed by PCI, including stenting, or to standard primary PCI without thrombectomy.…”
Section: Mechanical Cardioprotection Thrombus Aspirationmentioning
confidence: 68%
“…Two positive studies showing reduced infarct size 47,48 ; but there are 2 negative studies, 41,49 one of which was sizable 41 Intra-aortic balloon counterpulsation A large recent study showed no benefit on infarct size. 50 No benefit on clinical outcome in patients with cardiogenic shock 51 Rapid cooling…”
Section: Thrombus Aspirationmentioning
confidence: 99%